A prospective randomised multicentre trial comparing 10 Fr Teflon Tannenbaum stents with 10 Fr polyethylene Cotton–Leung stents in patients with malignant common duct strictures. Issue 3 (1st March 2000) - England, R E; Martin, D F; Morris, J; Sheridan, M B; Frost, R; Freeman, A; Lawrie, B; Deakin, M; Fraser, I; Smith, K
Abstract : BACKGROUND: Stent blockage is a multifactorial process in which stent design and materials, bacteria, proteins, and bile viscosity play a role. AIMS: To compare the patency of the 10 Fr Teflon Tannenbaum (TT) stent to that of the 10 Fr Cotton–Leung (CL) polyethylene stent with sideholes, in patients with malignant obstructive jaundice. METHODS: Patients were recruited to this prospective multicentre randomised study if they had a newly diagnosed malignant bile duct stricture below the hilum of the liver suitable for stenting with a 10 Fr stent. Data were collected and monitored by a professional monitoring company. Primary patency was the interval between stent placement and first exchange or death without recurrent jaundice. RESULTS: 134 consecutive patients were recruited between November 1994 and June 1997; 65 were randomised to the TT stent and 69 to the CL stent. Median patency and 95% confidence intervals were 181 (59, 303) days for the TT stent and 133 (92, 174) days for the CL stent, with no significant difference between the two stents (p=0.49). Median survival and 95% confidence intervals were 115 (71, 159) days for the TT stent and 151 (112, 190) days for the CL stent, with no significant difference between the two stents (p=0.765). CONCLUSION: Neither Teflon as a stent material nor the Tannenbaum design prolong the patency of plastic stents.